A survey on the effects of environmentally friendly soy protein inks on flexography print parameters in the packaging industry - SÖNMEZ, SİNAN (My University, 2022)
The synthetic resins in printing inks are harmful to the environment because they are not biodegradable and emit volatile organic compounds. The printing industry has sought alternative printing inks to solve these issues. The aim of the work is to explore sustainable and environmentally friendly inks, without scarifying ink performance. To determine their performance and effect on print quality, soy proteins were investigated. Also, commercial and formulated acrylic inks were used as reference inks. From the results, the print density of soy protein water-based inks is higher than that of the reference inks. Moreover, they obtained a higher print gloss than the reference inks. The printing contrast values of soy protein water-based inks are relatively low. There was no considerable difference found in TVI values. Overall, the soy protein water-based inks produced a very competitive result in printability and presented high potential for replace synthetic components in current commercial inks.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG); soybean; soy protein; resin; acrylic vehicle; ink; water based; flexographic; packaging